P301 L, an FTDP-17 mutant, exhibits enhanced glycation in vitro - Sonawane, Shweta Kishor; Chinnathambi, Subashchandrabose (Journal of Alzheimers Disease, 2020)
Background: Frontotemporal dementia and parkinsonism-linked to chromosome-17 are a group of diseases with tau mutations leading to primary tauopathies which include progressive supranuclear palsy, corticobas al syndrome, and frontotemporal lobar degeneration. Alzheimer's disease is a non-primary tauopathy, which displays tau neuropathology of excess tangle formation and accumulation. FTDP-17 mutations are responsible for early onset of AD, which can be attributed to compromised physiological functions due to the mutations. Tau is a microtubule-binding protein that secures the integrity of polymerized microtubules in neuronal cells. It malfunctions owing to various insults and stress conditions-like mutations and post-translational modifications. Objective: In this study, we modified the wild type and tau mutants by methyl glyoxal and thus studied whether glycation can enhance the aggregation of predisposed mutant tau. Methods: Tau glycation was studied by fluorescence assays, SDS-PAGE analysis, conformational evaluation, and transmission electron microscopy. Results: Our study suggests that FTDP-17 mutant P301 L leads to enhanced glycation-induced aggregation as well as advanced glycation end products formation. Glycation forms amorphous aggregates of tau and its mutants without altering its native conformation. Conclusion: The metabolic anomalies and genetic predisposition have found to accelerate tau-mediated neurodegeneration and prove detrimental for the early-onset of Alzheimer's disease.
Keywords: advanced glycation end products; Alzheimer's disease; FTDP-17; tau glycation